Making do in Damascus : navigating a generation of change in family and work - Gallagher, Sally K. (Contemporary issues in the Middle East., 2012)
Drawing on fieldwork that spans nearly twenty years, this book offers a rare portrayal of ordinary family life in Damascus, Syria. It explores how women draw on cultural ideals around gender, religion, and family to negotiate a sense of collective and personal identity. Emphasizing the ability of women to manage family relationships creatively within mostly conservative Sunni Muslim households, the author highlights how personal and material resources shape women's choices and constraints concerning education, choice of marriage partner, employment, childrearing, relationships with kin, and the uses and risks of new information technologies. The author argues that taking a nuanced approach toward analyzing women's identity and authority in society allows us to think beyond dichotomies of Damascene women either as oppressed by class and patriarchy or as completely autonomous agents of their own lives. Tracing ordinary women's experiences and ideals across decades of social and economic change, this book highlights the salience of collective identity, place, and connection within families, as well as resources and regional politics, in shaping a generation of families in Damascus.